2015
DOI: 10.1177/2050640614558344
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the barriers to the confident diagnosis of irritable bowel syndrome: A survey among general practitioners, gastroenterologists and experts in five European countries

Abstract: Background: The diagnostic processes for chronic abdominal conditions are challenging. Despite their tendency for diagnostic tests in patients with irritable bowel syndrome (IBS) symptoms, clinicians are encouraged to make a positive diagnosis based on symptom criteria without alarm signs. We explored how European physicians diagnose and manage patients suffering from IBS. Methods: We conducted a vignette-based survey to evaluate the diagnostic approaches in four standardized patients with IBS with constipatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
0
14
0
1
Order By: Relevance
“…Diarrhea, constipation and intestinal inflammation are the main symptoms of the patients with IBD and IBS [1112]. Clinical and epidemiological studies indicate that the inflammation is found from the jejunum to the rectum in both IBS and IBD [1314151617].…”
Section: Introductionmentioning
confidence: 99%
“…Diarrhea, constipation and intestinal inflammation are the main symptoms of the patients with IBD and IBS [1112]. Clinical and epidemiological studies indicate that the inflammation is found from the jejunum to the rectum in both IBS and IBD [1314151617].…”
Section: Introductionmentioning
confidence: 99%
“…With the pressure to increasingly acknowledge pathophysiological concepts and to refrain from solely symptom-based diagnosis the problems will rather increase. Based on the numerous putative biomarkers that are now discussed in IBS and FD (and some for both diseases) [20], doors are widely open for special examinations, however, for a clinically undefined subpopulation. This would cause a cost explosion, for which there are initial indications [21].…”
Section: Guidelines Should Guide Not Misguidementioning
confidence: 99%
“…Recent studies have shown that most clinicians continue to regard IBS as a diagnosis of exclusion. 12,30 Only 52% of gastroenterologists and 34% of PHCPs were confident diagnosing IBS based on symptoms, history and physical exam, with less than half of these confident to inform the patient without further investigations. 12 This is also supported by the reluctance of PHCPs to add IBS read-codes to patient records until more serious pathology was excluded.…”
Section: Discussionmentioning
confidence: 99%